The Role Of Digital Economic Transformation In The Rise Of Emerging Countries - Ebbini, Mohannad (جامعة الوادي - University of Eloued, 2022)
Abstract The purpose of this study is to shed light on the statement of digital transformation and its entry into all fields and economic activities, and to give examples in which digital transformation enters. The most important conclusions were that digital transformation increases the revenues of governments, institutions and companies and reduces costs and expenses. Furthermore, it works on the renaissance of these economies. In general, the researcher recommends that governments must speed up the provision of electronic services to citizens and work to increase these services and work as platforms for government electronic services to increase the activation of partnerships between the public and private sectors. As well, it is importance the use of modern technology in the light of these developments, as well as a plan and vision must be made for the coming years and benefit from developed countries in this field. الملخص الغرض من هذه الدراسة هو إلقاء الضوء على بيان التحول الرقمي ودخوله في جميع المجالات والأنشطة الاقتصادية ، وإعطاء أمثلة على ما يدخل فيه التحول الرقمي. ومن أهم الاستنتاجات أن التحول الرقمي يزيد من إيرادات الحكومات والمؤسسات والشركات ويقلل من التكاليف والنفقات. علاوة على ذلك ، فهو يعمل على نهضة هذه الاقتصادات. وبشكل عام يوصي الباحث بضرورة تسريع الحكومات في تقديم الخدمات الإلكترونية للمواطنين والعمل على زيادة هذه الخدمات والعمل كمنصات للخدمات الإلكترونية الحكومية لزيادة تفعيل الشراكات بين القطاعين العام والخاص. كما أنه من الأهمية بمكان استخدام التكنولوجيا الحديثة في ضوء هذه التطورات ، كما يجب وضع خطة ورؤية للسنوات القادمة والاستفادة من الدول المتقدمة في هذا المجال.
مقال
Keywords: Digital Economic ; Emerging Countries ; Digital Transformation